Investigation of the effect biodiesel-butanol-water fuel blend pressure on a single-cylinder diesel engine - Erdiwansyah, .; Mahidin, .; Ahmad Fitri, Yusop; Muhammad Zaki, .; R., Mamat; Muhibbuddin, .; Ratna Eko, Sardjono; Nor Azwadi, Che Sidik; Husni, Husin (Akademi Baru, 2021)
Energy demand from the community, which continues to increase has resulted in depletion of petroleum (fossil) energy in recent years. Many researchers have sought to find alternative fuels to replace dependence on conventional energy. The mixing of alcohol into diesel fuel has also been carried out by several previous researchers. The main focus of this research is to investigate the combustion performance of diesel engines using a mixture of biodiesel-butanol-water and diesel (B5Bu5W5). This research experiment used a single-cylinder diesel engine with different speeds at 25% and 50% engine load. The experimental results show that the maximum cylinder pressure reaches 72.32 bar when the engine load reaches 50%. While at 25% engine load press the maximum cylinder 33.62 bar. The heat dissipation for 50% engine load is also higher than the engine load 25% respectively 34.39% and 33.62%. Overall results show that cylinder pressure increases when the load and engine speed increase. However, the combustion time is a little slower than when using pure diesel fuel.